Prevalence of Undernutrition and Its Associated Factors Among Lactating Women in the Shebedino District, Sidama Regional State, Ethiopia - Yonas Hechera; Aregahegn Dona (SAGE Publishing, 2022)
Background : Ensuring the nutritional status of lactating women is crucial to prevent maternal morbidity and mortality in poor countries like Ethiopia. Hence, this study aimed to assess the prevalence of undernutrition and its associated factors among lactating women in Shebedino district, Sidama Regional State, Ethiopia. Methods : A community-based cross-sectional study was conducted among randomly selected 612 lactating women from February to March 2020. Data were collected by using an interviewer-administered, structured, and pretested questionnaire. Also, physical measurements (weight, height, and body mass index) were measured by using standardized and calibrated instruments. Data entered into Epi data version 3.1 and exported to SPSS version 23 for further analysis. Descriptive statistics, bivariable, and multivariable logistic regression analysis were done. A P-value of ≤ .05 was used to consider the statistical significance. Result : The prevalence of undernutrition was 25.9% (95% CI: 22.5, 29.5). Having polygamous husband (AOR = 3.47, 95% CI: 1.13, 10.68), belonged to households with less than 5 members (AOR = 1.81, 95% CI: 1.16, 2.83), abortion history in the last 6 months (AOR = 3.09, 95% CI: 1.73, 5.51), poor household wealth status (AOR = 3.85, 95% CI: 1.89, 7.81), and medium wealth status (AOR = 2.07, 95% CI: 1.06, 4.03) were factors positively associated with undernutrition. Conclusion : Undernutrition among lactating women was high in the study area. Attention should be given to the economic status of the women, family planning services, abortion prevention, and habits of marrying more than 1 wife (polygamy).